International Aspects of Investment Liberalization in the PRC: A Case of EU-China Cooperation - D. A. Potapov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines the role of investment cooperation and national foreign investment regime as a means to promote China’s economic and political interests and to respond to new global challenges that the country faces nowadays. To this end, the author examines the main stages of China’s liberalization of the legal regime for foreign investment from the end of the 1970s with a special focus on a new foreign investment law. In doing so the author attempts to link the evolution of investment regulation in the PRC with the dynamics of international relations development and the changing role of China as a regional and global actor. The author emphasizes that a trend towards the emergence of a polycentric world order not only provokes the rise of international tensions but also provides new incentives to promote dialogue and enhance cooperation between states and non-governmental actors, particularly by encouraging foreign investments. At the same time, there is a growing need to improve regulatory mechanisms for direct foreign investments. All these contradictory trends have directly affected China’s foreign investment regime reform. In this context the investment cooperation between the PRC and the European Union is of particular importance. The EU possesses a set of innovative technological solutions and competencies that are of particular interest to the Chinese leaders in the context of their efforts to modernize the country’s economy. The paper examines the volume, dynamics and key directions of investment flows between China and the EU member-states. The fact that after seven years of difficult negotiations, the EU and China managed to develop a special bilateral regulatory mechanism — EU-China Comprehensive Agreement on Investment — underscores again the importance of this cooperation for both parties. Even though the EU has suspended the ratification of this deal on the pretext of human right violations in the Xinjiang Uygur Autonomous Region, the author concludes, that in the future this agreement will come into force, since the very logic of the emerging polycentric world order urges for deeper cooperation between the EU and China. In this context, the investment regulation appears not only as a means to protect the Chinese economic interests, but also as an instrument to strengthen China’s international positions in the changing global context.